Characterization of neutralizing chimeric heavy-chain antibodies against tetanus toxin - Kexuan Cheng; Jiansheng Lu; Jiazheng Guo; Rong Wang; Lei Chen; Xi Wang; Yujia Jiang; Yating Li; Changyan Xu; Qinglin Kang; Gulisaina Qiaerxie; Peng Du; et al. (Human Vaccines & Immunotherapeutics)
Tetanus toxin (TeNT) is one of the most toxic proteins. Neutralizing antibodies against TeNT are effective in prevention and treatment. In this study, 14 anti-tetanus nanobodies were obtained from a phage display nanobody library by immunizing a camel with the C-terminal receptor-binding domain of TeNT (TeNT-Hc) as the antigen. After fusion with the human Fc fragment, 11 chimeric heavy-chain antibodies demonstrated nanomolar binding toward TeNT-Hc. The results of toxin neutralization experiments showed that T83–7, T83–8, and T83–13 completely protected mice against 20 × the median lethal dose (LD50) at a low concentration. The neutralizing potency of T83–7, T83–8, and T83–13 against TeNT is 0.4 IU/mg, 0.4 IU/mg and 0.2 IU/mg, respectively. In the prophylactic setting, we found that 5 mg/kg of T83–13 provided the mice with full protection from tetanus, even when they were injected 14 days before exposure to 20 × LD50 TeNT. T83–7 and T83–8 were less effective, being fully protective only when challenged 7 or 10 days before exposure, respectively. In the therapeutic setting, 12 h after exposure to TeNT, 1 ~ 5 mg/kg of T83–7, and T83–8 could provide complete protection for mice against 5 × LD50 TeNT, while 1 mg/kg T83–13 could provide complete protection 24 h after exposure to 5 × LD50 TeNT. Our results suggested that these antibodies represent prophylactic and therapeutic activities against TeNT in a mouse model. The T83–7, T83–8, and T83–13 could form the basis for the subsequent development of drugs to treat TeNT toxicity.